The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2174/18715230113129990014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Topical Black Seed Oil in the Treatment of Allergic Rhinitis

Abstract: Topical application of black seed oil was effective in the treatment of allergic rhinitis, with minimal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Similarly, Nikakhlagh et al showed the positive effects of NS oil capsule consumption over four weeks on the symptoms of allergic rhinitis, i.e., nasal mucosal congestion, nasal itching, runny nose, sneezing attacks, turbinate hypertrophy, and mucosal pallor [100]. Like the previous studies, that of Alsamarai et al demonstrated that nasal drops of NS oil, in comparison with nasal drops of ordinary food oil, could significantly improve the symptoms of AR patients, as well as their ability to tolerate exposure to allergens [47]. In that study, each drop comprised 15 mL of oil, and the patients applied 2 drops nasally (one in each nostril) 3 times daily for 6 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Nikakhlagh et al showed the positive effects of NS oil capsule consumption over four weeks on the symptoms of allergic rhinitis, i.e., nasal mucosal congestion, nasal itching, runny nose, sneezing attacks, turbinate hypertrophy, and mucosal pallor [100]. Like the previous studies, that of Alsamarai et al demonstrated that nasal drops of NS oil, in comparison with nasal drops of ordinary food oil, could significantly improve the symptoms of AR patients, as well as their ability to tolerate exposure to allergens [47]. In that study, each drop comprised 15 mL of oil, and the patients applied 2 drops nasally (one in each nostril) 3 times daily for 6 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…However, some patients with allergic rhinitis when treated using nasal drops of NS oil showed nasal dryness [47]. Dogar et al confirmed that side effects produced by treatment of children with acute lymphoblastic leukemia (ALL), aged between 2 – 18 years, with NS powder (40 mg/kg in two equal doses for 3 months), along with conventional therapy, were remarkably less than they were for L-asparaginase and conventional therapy (note: conventional therapy includes daunorubicin, vincristine, and prednisolone).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the 6 weeks treatment course, all of the patients in the mild active group became symptoms free; while in the moderate active group, 69% became symptoms free and 25% were improved; although in the severe active group, 58% became symptoms free and 25% were improved. Also, 92% of total patients in the active group demonstrated improvement in their symptoms or were symptoms free, and at the end of 6 weeks of topical use, the improvement in tolerability of allergen exposure in the active group was significant 176 . Nigellone suppressed symptoms in the majority of patients suffering from bronchial asthma when given orally 70 .…”
Section: Ns and Respiratory Diseasesmentioning
confidence: 94%
“…To date there were no curative treatment for AR, however, many pharmacotherapeutic treatment evaluated in different studies and suggested a variable clinical response [3]. Recently an interest was launched which is the evaluation of plant products in the treatment of allergic rhinitis [7].…”
Section: Introductionmentioning
confidence: 99%